Sexual identities and reproductive orientations: Coming out as wanting (or not wanting) to have children. (February 2021) - Pralat, Robert
In the context of growing visibility, recognition and acceptance of lesbian motherhood and gay fatherhood in countries such as Britain, it is important to ask how younger generations of sexual minorities approach the possibility of becoming a parent. Drawing on interviews with lesbians and gay men who do not have children but may have them in the future, I explore how people become aware that having children is an option. By attending to how this consciousness manifests in conversations and how conversations shape the consciousness, I illuminate specific dynamics that raising the topic of parenthood creates in intimate interactions. My data show that it is often unclear to men and women who form same-sex relationships whether they are socially expected to have children. I argue that this ambiguity requires a kind of 'coming out' through which feelings about parenthood are made explicit. Using the concept of coming out, I ask: What if we were to think of people in terms of their 'reproductive orientations' rather than sexual identities? I suggest that, similar to expressing sexual identities, articulating reproductive orientations involves aligning with particular life trajectories based on binary logic. However, with ambiguous expectations about parenthood, neither having children nor remaining childfree is explicitly normative. As such, unlike coming out as lesbian or gay, which transgresses norms surrounding sexuality, coming out as wanting or not wanting to have children challenges normativity itself. I reflect on how this 'normative challenge' makes it possible to imagine parenthood and 'childfreedom' as intimacies of equal value.